Granuloma Inguinale - Adi Agung Anantawijaya D; Muhammad Izazi Hari Purwoko; Mutia Devi; Suroso Adi Nugroho (HM Publisher, 2021)
Granuloma ingunale (GI) or donovanosis is a genital ulcer disease caused by theCalymmatobacterium granulomatis. It is a Gram-negative, facultative, obligateintracellular and pleomorphic bacterium. This bacterium has phylogeneticallyclosed to and placed within the Klebsiella genus. Clinically, the disease is com-monly characterized as painless, slowly progressive ulcerative lesions on thegenitals or perineum without regional lymphadenopathy. The lesions are highlyvascular and bleed easily on contact Extragenital lesions may occur but are rareand more common in newborns from mothers with GI genital lesions. Thisdisease is often neglected, therefore it is often misdiagnosed and inaccuratetherapy. Treatment time is 3 weeks or until clinical cure has been achieved forall proposed regimens. It often occurs both in men and women of reproductiveage (20-40 years). This article consists of several theoretical references that havebeen viewed to have a better understanding of GI.